Sarcoglottis wernerherzogii (Spiranthinae), a new species from Cusco, Peru: addenda - Collantes, Benjamín (2024)
A comparative table between Sarcoglottis wernerherzogii, S. fasciculata, and other species of the genus present in Peru, is included.